Long-term Preservation of Electronic Information Objects – Comparative Analysis of the Research on the Application of Theoretical Models - Stančić, Hrvoje (2006)
The paper analyses the results of an international study on the preservation strategies and techniques conducted by Cloonan and Sanett through the InterPARES project in the year 2000 and compares them with the results gathered five years later by the similar research among the institutions in Croatia. The reason for the recent study was to identify, analyse and compare the preservation strategies and techniques used in Croatia with those used worldwide taking into account the five-year gap between the two surveys, as well as to check on the level of awareness of the need for proactive care of the digital collections. By analysing the data and synthesising the results the author arrives at the conclusion at three different levels – the level of comprehension of the term “ preservation” , the level of application of the preservation procedures, and the level of preservation policies and practices.
ENG